1992
DOI: 10.1515/bchm3.1992.373.2.1079
|View full text |Cite
|
Sign up to set email alerts
|

Neurohypophysial Vasopressin and Oxytocin as Influenced by (6R)-5,6,7,8-Tetrahydro-α-Biopterin in Euhydrated and Dehydrated Rats

Abstract: Experiments were performed to test a possible role of (6 J R)-5,6,7,8-tetrahydro-a-biopterin dihydrochloride (BH4) in the neurohypophysial vasopressin and oxytocin content in euhydrated and dehydrated rats. Chronic treatment with BH4, administered to not dehydrated animals, was followed by a significant decrease of neurohypophysial vasopressin, but not of neurohypophysial oxytocin. In dehydrated animals the neurohypophysial vasopressin content decreased progressively; this process was not affected significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
1
11
1
Order By: Relevance
“…Similar findings were obtained in other studies as well (Marcisz et al, 2001;Vargas et al, 1991). In another study performed by Ciosek (2002) it was found that intravenous administration of TRH in different doses indicated different effects depending on the dose, and that 100 ng/100 g dose TRH administration increased plasma AVP levels while decreasing hypothalamic and neurohypophysial AVP amount. And in another study, it was reported that neurohypophysial AVP increased while plasma AVP levels did not elevated (Ciosek and Drobnik, 2004).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Similar findings were obtained in other studies as well (Marcisz et al, 2001;Vargas et al, 1991). In another study performed by Ciosek (2002) it was found that intravenous administration of TRH in different doses indicated different effects depending on the dose, and that 100 ng/100 g dose TRH administration increased plasma AVP levels while decreasing hypothalamic and neurohypophysial AVP amount. And in another study, it was reported that neurohypophysial AVP increased while plasma AVP levels did not elevated (Ciosek and Drobnik, 2004).…”
Section: Discussionsupporting
confidence: 88%
“…It is accepted that thyroid gland hormones, triiodothyronine and thyroxin are effective on liquid-electrolyte balance and its regulation, as they are effective on general metabolism. (Ciosek, 2002;Ali et al, 1988;Dakine et al, 2000). Different results were obtained in the studies, in which the vasopressin and thyroid hormone relation was searched and these mechanisms could not certainly be revealed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations